Fetal ovarian cyst in the 37th week of pregnancy: a case report - Basirat, Zahra; Nejadgholi, Mehdi (Journal of Reproduction & Infertility, 2006)
Introduction: Fetal ovarian cysts are rare abdominal tumors with unknown pathogenesis. They may be diagnosed accidentally during ultrasonography. Fetal ovarian cysts pose the risk of rupture or torsion with subsequent loss of the affected ovary. Diagnosis and appropriate management reduce acute and long-term complications. Case Report: The case was the fetus of a 26 year old primigravida in the 37th week of gesta-tion in Babol in 2005. A unilateral fetal simple ovarian cyst with a diameter of 30 mm was diagnosed during ultrasonography. The case was delivered by cesarean section due to fetal distress a week later. The neonate was followed up after birth and the cyst was spontaneous-ly disappeared after 45 days. Conclusion: In fetal ovarian cysts, there may be good outcomes following conservative man-agement. After delivery, decrease of hormonal stimulation may lead to the spontaneous reso-lution of ovarian cysts. Surgical procedures are performed if complications such as trosion or rupture of the cyst develop.
Keywords: Fetal ovarian cyst; Sonography; Pregnancy; Abdominal mass; Abdominal tumors; Ovarian torsion; Cyst rupture